Tumor-associated glycoprotein-mediated suppression of immune-responses and their potential impact on protective immunity against sexually-transmitted infections in the female genital tract - Cutay, Sandra Jelyn G.; Ibana, Joyce A. (Quezon City Institute of Biology, College of Science, University of the Philippines Diliman, 2016)
Immune suppression occurs both in tumor microenvironments and in the female eproductive tract (FRT) during the secretory phase of the menstrual cycle. In tumors, this allows cancer cell to evade antitumoral responses. In FRT, this promotes an immunological milieu that is conductive for conception, but also makes it more vulnerable to microbial infections. Previous reports suggested that a tumor-associated glycoprotein-72 (TAG-72) induces the expression of Th2 cytokines by antigen presenting cell at the fetal-maternal interface. TAG-72 is a 10 kD glycoprotein with mucin-like biochemical and biophysical properties. It is expressed at elevated levels in metastatic tumors and in the endometrium during the secretory phase of the menstrual cycle. In this study, we found that TAG-72: 1) downregulates perforin expression in Natural Killer (NK) cells2) inhibits NK cell proliferation,3) skews cytokine expression to a Th2 profile, and 4) dampens some immune responses to lipopolysaccharide (LPS) stimulation. These results indicate that TAG-72 induces the suppression of some immune functions in tumor microenvironments and in the FRT. Elucidating the role of TAG-72 in the cyclical nature of immune suppression in the FRT may provide imprtant insights for designing novel cancer immunotherapeutic strategies that can restore immune competence in tumor microenvironments.
Thesis (M.S. Microbiology)--University of the Philippines Diliman
Keywords: Generative organs, Female -- Infections; Sexually transmitted diseases